Research highlights: microfluidic analysis of antimicrobial susceptibility. Issue 5 (7th March 2015) - Murray, Coleman; Adeyiga, Oladunni; Owsley, Keegan; Di Carlo, Dino
<x xml:space="preserve">Abstract</x> Single-cell morphological analysis – gradient antibiotic susceptibility – rapid bacterial detection in blood.